TAK1: A Molecular Link Between Liver Inflammation, Fibrosis, Steatosis, and Carcinogenesis - Wang, Weijun; Gao, Wenkang; Zhu, Qingjing; Alasbahi, Afnan; Seki, Ekihiro; Yang, Ling (Frontiers in Cell and Developmental Biology, 2021)
Chronic insult and persistent injury can cause liver inflammation, fibrosis, and carcinogenesis; it can also be associated with metabolic disorders. Identification of critical molecules that link the process of inflammation and carcinogenesis will provide prospective therapeutic targets for liver diseases. Rapid advancements in gene engineering technology have allowed the elucidation of the underlying mechanism of transformation, from inflammation and metabolic disorders to carcinogenesis. Transforming growth factor-β-activated kinase 1 (TAK1) is an upstream intracellular protein kinase of nuclear factor kappa-B (NF-κB) and c-Jun N-terminal kinases, which are activated by numerous cytokines, growth factors, and microbial products. In this study, we highlighted the functional roles of TAK1 and its interaction with transforming growth factor-β, wingless, AMP-activated protein kinase, and NF-κB signaling pathways in liver inflammation, steatosis, fibrosis, and carcinogenesis based on previously published articles.